A Study on Political Policies of Mughals: Exploring the Territorial Boundaries and Administrative Divisions of Mughal Province of Awadh (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Mughal province of Awadh extended over the territory entirely consisting of alluvial plains, lying between 79.6o and 940 longitudes E. and 260 and 28.4 latitude N. The limits of the suba are described by Abul Fazl in his Account of Twelve Provinces' It was bounded on the east by the province of Bihar and to the north lay the Northern mountains; sarkar Manikpur of suba Allahabad was situated on the south of the province, while on the western side was sarkar of Kannuj of suba Agra. The distance from; sarkar Gorakhpur to Kannuj was computed at 135 while only 115 kos were said to separate the northern mountains and the southern boundary of the suba.